Improving health-promoting self-care in family carers of people with dementia: a review of interventions - De Oliveira, Deborah; Sousa, Lidia; Orrell, Martin (Dove Medical Press, 2019)
Background: Providing care for a family member with dementia can leave little time for carers to look after their own health needs, which makes them more susceptible to mental and physical health problems. This scoping review aimed to explore potential health benefits of interventions aimed at improving health-promoting self-care in family carers of people with dementia.